A value-of-information approach to measuring risk in multi-period economic activity - Pflug, Georg Ch. (Journal of Banking & Finance, 2006)
In this paper, we discuss measures of risk for uncertain outcomes of economic activity, which are based on the notion of the value of full information in stochastic programs. Information is measured in terms of σ-algebras. For multi-period income streams information is represented by filtrations, i.e. sequences of σ-algebras. The basic properties of our risk measures are multi-period coherence (“diversification decreases risk”), compound concavity (“random alternatives increase risk”) and convex monotonicity (“insurance decreases risk”).